2022
DOI: 10.4236/jcdsa.2022.122010
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Pathway Involvement in the Beneficial Skin Effects of Moderate Ionic Osmotic Stress—The Case of The Dead Sea Water

Abstract: Objectives: Exposing skin to moderate ionic osmotic stress (MIOS) triggers several biochemical responses. The objective of this work is to reveal the mechanism triggered by MIOS on the skin surface. Furthermore, this work aims to study the involvement of the Nrf2 (nuclear factor erythroid-2-related factor 2) pathway, activated by MIOS, and its beneficial effect in protecting skin against stress via the stimulation of phase II enzymes. Methods: HaCaT cells and human skin organ culture were exposed to Dead Sea W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This regulated antioxidant mechanism has been demonstrated to play a role in the treatment of several skin diseases 39 . In our previous study, we demonstrated that topical exposure of HSOC to DS water results in the induction of the Nrf2‐Keap1 pathway, likely due to the high mineral content of DS water acting as moderated ionic osmotic stress (MIOS) 16 . Here, we elucidate the effect of solar irradiation at the DS on cutaneous tissue.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This regulated antioxidant mechanism has been demonstrated to play a role in the treatment of several skin diseases 39 . In our previous study, we demonstrated that topical exposure of HSOC to DS water results in the induction of the Nrf2‐Keap1 pathway, likely due to the high mineral content of DS water acting as moderated ionic osmotic stress (MIOS) 16 . Here, we elucidate the effect of solar irradiation at the DS on cutaneous tissue.…”
Section: Discussionmentioning
confidence: 89%
“…39 In our previous study, we demonstrated that topical exposure of HSOC to DS water results in the induction of the Nrf2-Keap1 pathway, likely due to the high mineral content of DS water acting as moderated ionic osmotic stress (MIOS). 16 Here, we elucidate the effect of solar irradiation at the DS on cutaneous tissue. As shown in Figure 5 and Table 1, the UVB solar radiation (280-320 nm) intensity at the DS is lower than in Jerusalem by 5.4% due to the altitude difference between these locations, measured by our spectrophotometer instrument (UV-VIS Ocean Optics USB2000+ Extended Range Spectrophotometer, Largo, FL USA).…”
Section: Comparison Of Cell Integrity Following Exposure To Solar Rad...mentioning
confidence: 99%
See 3 more Smart Citations